Wissensmanagement in Feuerwehren skalierbare IT-Architektur für Erweiterung und Austausch - Schultz, Andreas Maximilian; Mozgova, Iryna

Rezension zu: „The Nordic Bible. Bible Reception in Contemporary Nordic Societies“ - Bergmann, Claudia Dorit (tà katoptrizómena – Magazin für Kunst | Kultur | Theologie | Ästhetik 147)

Weather-induced emergency situations: Extreme data in situational awareness and visualisation - Gräßler, Iris; Pottebaum, Jens; Hieb, Michael; Pratzler-Wanczura, Sylvia; Krüger, Oliver; Kruijff, Ivana; Rupp, Nicola (Proceedings of the Days of Security Research 2023)
Extreme weather situations increasingly lead to hazardous situations with high demands on de-cision-making and communication. Weather and impact forecasts serve to prepare for such an emergency situation, and extreme data must be processed during operations. Therefore, extreme data is categorised with reference to global weather data and data from local situation reconnais-sance using sensors carried by mobile robots. A concept is presented in which information quality is explicitly considered in visualization for situational awareness. This extends existing principles of information visualisation with regard to the uncertainty resulting from extreme data. The re-sults are intended to help decision-makers at different management levels to make informed decisions.

Experimentelle und numerische Analyse des Fließverhaltens von hochviskosen Wärmeleitstoffen im Fertigungsprozess - Gröger, Benjamin; Wiebicke, Felix; Koch, Ilja; Gude, Maik; Gilich, Julian; Meschut, Gerson (24. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

N2O oxidized combustion of ethylene: Detailed laminar flame structure and the significance of oxidizer decomposition kinetics for modeling - Hoener, Martin; Bierkandt, Thomas; Shaqiri, Shkelqim; Kasper, Tina (Proceedings of the Combustion Institute)

ADMM-TGV image restoration for scientific applications with unbiased parameter choice - Zietlow, Christian; Lindner, Jörg (Numerical Algorithms)

Vermittlungshorizonte. Erziehungswissenschaftliche Reflexionen über hochschul- und wissenschaftsdidaktische Herausforderungen - Freitag, Christine (Wissenschaftsdidaktik als kritische Kommunikationsanalyse. Ein Sammelband zur Weiterführung eines Gedankens von Ludwig Huber)

Der Briefroman als Medium weiblicher Kritik in der Aufklärung – Einblicke in Caroline Rudolphis »Gemälde weiblicher Erziehung« - Vochatzer, Stefanie (»Debattieren, Opponieren, Protestieren – Interdisziplinäre Perspektiven auf sprachliche Praktiken des Widersprechens«)

Efficient Shape Formation by 3D Hybrid Programmable Matter: An Algorithm for Low Diameter Intermediate Structures. SAND 2024: 15:1-15:20 - Scheideler, Christian; Hinnenthal , Kristian; Liedtke, David Jan

Polylogarithmic Time Algorithms for Shortest Path Forests in Programmable Matter. - Scheideler, Christian; Padalkin, Andreas

Universal Coating by 3D Hybrid Programmable Matter. - Scheideler, Christian; Kostitsyna, Irina; Liedtke, David Jan

The structural power of reconfigurable circuits in the amoebot model. - Scheideler, Christian; Padalkin, Andreas; Warner, Daniel (The structural power of reconfigurable circuits in the amoebot model. Nat. Comput. 23(4): 603-625 (2024))

Routing schemes for hybrid communication networks. - Scheideler, Christian; Coy, Sam; Czumaj, Arthur; Schneider, Philipp; Werthmann, Julian (Routing schemes for hybrid communication networks. Theor. Comput. Sci. 985: 114352 (2024))

Invited Paper: Blockchains made Lightweight: A Median Rule for State Machine Replication. - Scheideler, Christian; Dou, Jinfeng

Reconfiguration and Locomotion with Joint Movements in the Amoebot Model. - Scheideler, Christian; Padalkin, Andreas; Kumar , Manish

„Und ich sag mal, Theorie und Praxis ist zweierlei” – Wie können Praxisphasen Lehramtsstudierende auf zukünftige Anforderungen vorbereiten? - Vernholz, Mats; Jonas-Ahrend, Gabriela

Sodium 4-styrenesulfonyl(trifluoromethanesulfonyl)imide-based single-ion conducting polymer electrolyte incorporating molecular transporters for quasi-solid-state sodium batteries - Wunder, Clemens; Lai, Thanh-Loan; Šić, Edina; Gutmann, Torsten; Vito, Eric; Buntkowsky, Gerd; Zarrabeitia, Maider; Passerini, Stefano (Journal of Materials Chemistry A)
Sodium batteries are an attractive alternative for future energy storage as they can be produced with abundant and low-cost materials. Nonetheless, sodium-ion batteries (SIBs) are often composed of flammable and volatile carbonate-based liquid electrolytes. Polymer electrolytes have attracted significant attention as safer alternatives. Among polymer electrolytes, single-ion conductive polymer electrolytes (SIPEs) are considered particularly interesting because they can suppress dendrite growth, enabling high-performance (quasi)-solid-state sodium–(metal) batteries. In this work, a self-standing, flexible, quasi-solid-state SIPE is investigated, which is composed of sodium 4-styrene sulfonyl (trifluoromethanesulfonyl) imide (NaSTFSI), pentaerythritol tetrakis(3-mercaptopropionate) (PETMP) and pentaerythritol tetraacrylate (PET4A) blended with poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP). The SIPE membrane, including 50 wt% of molecular transporter, exhibits ionic conductivity of 1.4 × 10−5 S cm−1 and 1.3 × 10−4 S cm−1 at 20 °C and 90 °C, respectively, thermal stability up to 280 °C, electrochemical stability window up to 4.5 V vs. Na/Na+, and Na plating/stripping reversibility in symmetric Na‖Na cells. The manufactured SIPE implemented in Prussian White (PW)‖Na cells enables the delivery of 147 mA h g−1 of PW at 15 mA g−1 with a Coulombic efficiency of over 99%, which is comparable with the PW‖Na cells using liquid carbonate electrolyte, confirming the suitability of the designed SIPE for sodium–(metal) batteries.

Novel Heterogeneous Pd Catalysts for Cross-Coupling Reactions in Biocompatible Media: Structural Insights from Solid-State NMR Techniques - Wissel, Till; Rösler, Lorenz; Brodrecht, Martin; Höfler, Mark V.; Herr, Kevin; Oliveira Jr., Marcos; Klimavicius, Vytautas; Ebert, Martin; Breitzke, Hergen; Hoffmann, Markus; Buntkowsky, Gerd; Gutmann, Torsten (ChemCatChem)
Abstract Novel SBA-15-supported heterogeneous catalysts are synthesized and applied in the Mizoroki?Heck and the Suzuki?Miyaura cross-coupling reactions in green solvents like PEG or water. The structural properties of the products after each synthesis step are monitored by different analytics. The amount of amine/carboxyl groups and vanillin/histidine methyl ester and thermal stability are determined by TGA and elemental analysis, while ICP-OES delivered the amount of palladium of the catalysts. The morphology is investigated by SEM and XPS and confirms the presence of coordinated palladium in the zero-oxidation state. Gas adsorption analysis is conducted, which indicates the presence of palladium clusters in one of the two catalysts, which is underlined by BSE images combined with EDX. A detailed 13C ssNMR and DNP-enhanced 15N ssNMR spectral analysis is presented, which provides ultimate proof of the successful syntheses of the catalysts. The coordination of the palladium onto the carrier material is shown by combining the NMR spectral results with the results of the other analytics. First catalytic tests show for the Mizoroki?Heck reaction yields up to nearly 100% and for the Suzuki-Miyaura up to 88% in the presence of PEG and water, respectively.
Keywords: SBA-15; Heterogeneous catalyst; Pd cross-coupling; Polyethylene glycol; Solid-state DNP NMR

Towards Routine 7Li In Situ Solid-State NMR Studies of Electrochemical Processes in Li\textbarLiPF6\textbarLFP Cells - Šić, Edina; Fredericks, Dominion; Pecher, Oliver; Wegner, Sebastian; Breitzke, Hergen; Singh, Vickram; Buntkowsky, Gerd; Gutmann, Torsten (Applied Magnetic Resonance)
In this study, electrochemical processes in a Li{|}LiPF6{|}LFP cell have been explored applying advanced solid-state NMR technologies. In situ solid-state NMR allows to monitor structural changes in local environments in commercially available cell components during galvanostatic cycling. In collaboration with Dragonfly Energy, ePROBE GmbH and Bruker BioSpin GmbH & Co. KG, we have demonstrated an experimental procedure for routine application of in situ solid-state NMR for battery research. This points out the high potential of this approach for use in the energy storage industry.

At the limits of bisphosphonio-substituted stannylenes - Nasemann, Sina; Franz, Roman; Kargin, Denis; Bruhn, Clemens; Kelemen, Zsolt; Gutmann, Torsten; Pietschnig, Rudolf (Chemistry - An Asian Journal)
Abstract Donor stabilization of Sn(II) and Pb(II) halides with 1,1?-ferrocenylene bridged bisphosphanes has been explored for Fe(C5H4P(C6H5)2)2 (dppf), and Fe(C5H4PH(C4H9))2. These bisphosphanes are reacted with SnBr2 and PbCl2 with and without additional Lewis acid (AlCl3) forming acyclic and cyclic donor adducts from which the latter represent bisphosphoniotetrylenes. Since dynamic exchange in solution is observed, characterization includes solution and solid-state NMR in addition to SC-XRD, amended by DFT calculations.
Keywords: ferrocene; lead; phosphorus; tetrylene; tin